Pneumatosis Coli Formation via Counterperfusion Supersaturation in a Patient with Severe Diarrhea. (5th August 2018) - Vecchio, Eric; Jamot, Sehrish; Ferreira, Jason
Abstract : We present the case of an elderly male patient with known multiple myeloma who was hospitalized with profuse watery diarrhea and abdominal pain after a course of induction chemotherapy. Intestinal intramural gas was found on imaging and the diagnosis of pneumatosis intestinalis was confirmed by colonoscopy. We propose counterperfusion supersaturation as the etiology for this patient's pneumatosis coli via disruption of homeostasis between nitrogen and hydrogen normally present in the bowel. His condition was successfully treated with antidiarrheal medications and inhaled oxygen as well as intravenous hydration, and he eventually completed multiple myeloma directed chemotherapy with an excellent response. In this report, we discuss how clinicians can improve management of pneumatosis intestinalis by understanding the proposed pathophysiology.